Substitucion de concentrado industrial por harina de yuca, en dos niveles, para alimentar pollo en ceba - Rodríguez G, H.; Ospina, B.; Buitrago, J.; Oquendo, G.; Almaguer, N.; Rodríguez P., N. (1990)
Two levels of CM substitution (25 and 50 percent) for industrial concentrate were studied; 3 treatments (with broiler chicks randomly assigned to blocks) during fattening were compared with a check treatment (100 percent industrial concentrate). Slaughter wt. over 1.5 kg/animal were obtained, with the fattening period lasting from 50 to 62 days for the treatments assessed. The cost/kg feed was 0.25, 0.21, and 0.17 peso for the industrial concentrate, 75 percent industrial concentrate/25 percent CM, and 50 percent industrial concentrate/50 percent CM, resp. Likewise, fattening costs $0.10/animal less in treatment 2. (AS-CIAT)